Work life and family life connection among nurses and police personnel a research report - Ishak, Salma; Musa, Mohd Makzan; Ahmad, Abd Halim (Universiti Utara Malaysia, 1996)
The purpose of this study was to examine the interrelationship among stress, satisfaction , and coping behaviors within the context of work life and home life as perceived by two groups of workers representing the human service sector. A total of 380 respondents, comprising of 198 nurses and 182 police personnel, provided the data which were gathered through a self-administered questionnaire. Nurses were selected from those employed in a large hospital in Kuala Lumpur; while police personnel were selected from among those attached to four police stations in the Kuala Lumpur area. Analyses of the data revealed that both groups did not differ very much in terms of their responses. They reported average level of stress in relation to their jobs, average amount of satisfaction from their jobs, and higher frequency of using the control style of coping in dealing with problems arising from work. Satisfaction with family life was reported to be higher than that of satisfaction with their jobs. Nevertheless, both groups of respondents reported experiencing an average amount of conflict between work life and home life, with spillover from work to family life occurring more frequently than spillover from family to work life. In terms of the interrelationships among the major variables and selected demographic factors, generally, the correlations were in the expected directions although the magnitude ranged from low to moderate. Significant positive correlations were found among stress experienced from work, work-home conflict, work-to-family spillover, and family-to-work spillover. Significant negative correlations were found between job and family-derived satisfactions with stress from job, work-home conflict, and spillover between work and family life. With regards to demographic and other job and family related factors, the responses were mixed for nurses and police personnel. Very few agreements were found between the nurses and police personnel suggesting that different factors were influencing the stress and satisfaction experienced from their job and family life. As such, in formulating policies to enhance employees work life and family life, individual organizations should consider factors that are uniquely applicable and of significance to their particular group of employees.